BIODEGRADABLE POLYMER COMPOSITE BASED ON POLYVINYL CHLORIDE AND WOOD WASTE. DEVELOPMENT AND CHARACTERIZATION - VLAD BARBULESCU; LAURENTIA ALEXANDRESCU; MIHAELA NITUICA; MIHAI GEORGESCU; MARIA SONMEZ; DANIELA-MARIA STELESCU; DANA GURAU (Journal of Engineering Studies and Research)
This work deals with the development and characterization of biodegradable polymer composites based on of polyvinyl chloride (PVC) and wood waste (WW) post-consumer waste. Wood waste resulting from wood processing into finished products is cryogenically ground to min. 500 nm, mechanically functionalized at temperature with polydimethylsiloxane (PDMS) (7%) and compounded in varying proportions (10%, 20%, 50%). The new composite is biodegradable due to the compounding with wood fibers, have low density and implicitly the products made from, a lower weight, reduced costs and recover waste. Soles for shoes will be processed by injection using these materials.